Urinary incontinence, knowledge and attitudes in São Paulo - Blanes, L.; Pinto, R. C.T.; Santos, V. L.C.G. (My University, 2001)
Purpose: The urinary incontinence (UI) constitutes an important problem that affects great part of the population. The apparent misinformation about the subject aimed us to study the knowledge and attitudes of people aged 55 years or older about the UI. Material and Methods: Between June and November 1999, 400 men and women, living in São Paulo city had been interviewed. For this, it was used an Incontinence Quiz validated by Branch et al. (1994), that consists of 14 statements (6 correct and 8 incorrect) grouped in 4 UI categories: treatment and effects; causes; relationship of aging and physician/patient discussion about the UI. These statements could be answered as: I agree, I disagree or I don't know. Results: The results show that only for the two statements we obtained correct indexes of almost 60% (66% for the affirmative 2, related to the cure and recovery of the UI; and 61% for the affirmative 5, related to the greater risk of woman to develop UI), remaining the other between 30% and 41%. For the incorrect affirmative, the index varied from 23% to 43% of correct answers. Although the higher level of school age had presented significant statistics association with the hit of 2 from 14 statements, these are related to specific aspects of causes and treatments of UI. Conclusions: The results showed a reality marked by misinformation and negative attitudes of the interviewed toward the loss of urinary control, what involves the necessity of educational interventions for the population, making possible the availability of solutions for this problem.
Keywords: Behavioral approach; Data collection; Urinary incontinence